Implementation of Science and Technology-Based Guidance and Counseling Services to Improve the Effectiveness of Guidance and Counseling Teacher Performance at SMAN 1 Telagasari - Fanya Azzahro; Azizah Ramadhani; Candra Indra Prahasta; Dinda Meliana Alwahib (Penerbit Hellow Pustaka, 2025)
This study aims to describe the implementation of science and technology-based guidance and counseling (BK) services in improving the effectiveness of BK teachers' performance at SMAN 1 Telagasari. The method used is a qualitative approach with direct observation techniques and in-depth interviews with BK teachers and students. The BK services studied cover personal, social, career, and learning areas, with programs such as career guidance, individual and group counseling, and classical guidance. The results show that the use of technology, such as Google Forms in the Problem Checklist (DCM) and data processing applications, significantly helps BK teachers in identifying student needs quickly and systematically. The main supporting factors are stakeholder support and facilities, while obstacles include limited teacher digital competence and low student openness. It is concluded that the implementation of science and technology-based BK services at SMAN 1 Telagasari is able to improve the effectiveness of BK teachers' performance in aspects of assessment, management, and student accessibility, although it needs to be strengthened in technology mastery and efforts to build student trust in counseling services.